An Unstable Competence-Induced Protein, CoiA, Promotes Processing of Donor DNA after Uptake during Genetic Transformation in Streptococcus pneumoniae - Desai, Bhushan V. (American Society for Microbiology, 2006)
Natural genetic transformation in Streptococcus pneumoniae entails transcriptional activation of at least two sets of genes. One set of genes, activated by the competence-specific response regulator ComE, is involved in initiating competence, whereas a second set is activated by the competence-specific alternative sigma factor ComX and functions in DNA uptake and recombination. Here we report an initial characterization of CoiA, a ComX-dependent gene product that is induced during competence and is required for transformation. CoiA is widely conserved among gram-positive bacteria, and in streptococci, the entire coiA locus composed of four genes is conserved. By use of immunoblot assay, we show that, similar to its message, CoiA protein is transient, appearing at 10 min and largely disappearing by 30 min post-competence induction. Using complementation analysis, we establish that coiA is the only gene of this induced locus needed for transformability. We find no indication of CoiA having a role in regulating competence. Finally, using (32)P- and (3)H-labeled donor DNA, we demonstrate that a coiA mutant can internalize normal amounts of donor DNA compared to the wild-type strain but is unable to process it into viable transformants, suggesting a role for CoiA after DNA uptake, either in DNA processing or recombination.